Implementasi public relations dalam angkringan membangun citra dan hubungan dengan pelanggan: Studi kasus di Angkringan Seven Legend Kota Blitar - Yahya, Syafi’ Ainul (Maliki Interdisciplinary Journal, 2023)
This research discusses the implementation of Public Relations (PR) in angkringan, a coffee shop that has become an iconic culinary symbol in Indonesia. Angkringan has evolved into a cultural emblem, a meeting place, and a platform for discussions, influencing its image, customer engagement, and community relationships. PR plays a pivotal role in understanding, shaping, and maintaining the image of angkringan, as well as nurturing positive relationships with customers and the community. Through a case study of Angkringan Seven Legend in Blitar City, the research employs qualitative methods and in-depth interviews to uncover effective PR practices. The findings provide valuable insights for angkringan owners and PR practitioners, contributing to a better understanding of PR in the culinary industry.